If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y = 3y + 5 Reorder the terms: -2y = 5 + 3y Solving -2y = 5 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -2y + -3y = 5 + 3y + -3y Combine like terms: -2y + -3y = -5y -5y = 5 + 3y + -3y Combine like terms: 3y + -3y = 0 -5y = 5 + 0 -5y = 5 Divide each side by '-5'. y = -1 Simplifying y = -1
| -12=3x+9-6x | | 25-3x=1 | | 2(l+0.4l)=364 | | 56-(3c+4)=4(c+7)+3 | | 0.07y+0.02x=5 | | 9x-12+85=0 | | -3/4r-1 | | U^2-3v=0 | | -z/2 | | (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 | | 8+4v=-4 | | 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 | | (2y+9)(2y+9)=81 | | (4-2j)/(2-1j) | | 5.26s-2.01=-8.94 | | -2g+7= | | -9s+18-18=18s-4-2 | | 7v+224=-84v | | 3v+9+v=2v-2+3 | | -38-37= | | 10+5x-x=10+4x+4 | | 45=26+b | | X+2+x-10=90 | | 2v+1=-3v+8v+10 |